1990
DOI: 10.1111/j.1365-2761.1990.tb00797.x
|View full text |Cite
|
Sign up to set email alerts
|

The effects of trichlorfon, praziquantel and copper sulphate on various stages of the monogenean Benedeniella posterocolpa, a skin parasite of the cownose ray, Rhinoptera bonasus (Mitchill)

Abstract: Monogeneans of the superfamily Capsa)oidca have been a severe problem in maintaining both teleosts and elasmobranchs in eaptivity. Infestations of Benedeniella posterocolpa on the skin of the cownose ray, Rhinoptera bonasus, provided an excellent model for testing the effects of triehlorfon (0-7ppm), praziquantel (20ppm) and eopper sulphate (0-25 ppm) on adult monogeneans in situ, and on adult monogeneans. oncomiraeidia and eggs in vitro. One treatment with praziquantel eliminated i(K)% of the worms from the s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

3
30
1

Year Published

2000
2000
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 49 publications
(34 citation statements)
references
References 9 publications
3
30
1
Order By: Relevance
“…This result was similar to that shown by Thoney (1990) who demonstrated that trichlorfon killed all B. posterocolpa within 21 h in vitro, but did not prevent egg laying. In this study, trichlorfon at a concentration of 2.5 mg/L was the most effective drug tested in vivo.…”
Section: Discussionsupporting
confidence: 91%
See 3 more Smart Citations
“…This result was similar to that shown by Thoney (1990) who demonstrated that trichlorfon killed all B. posterocolpa within 21 h in vitro, but did not prevent egg laying. In this study, trichlorfon at a concentration of 2.5 mg/L was the most effective drug tested in vivo.…”
Section: Discussionsupporting
confidence: 91%
“…Therefore, in the present study the effects of various treatments on the egg hatching and embryonic development of D. vastator were also investigated. Previously praziquantel was shown to be ineffective for reducing the hatching success or inhibiting the embryonic development of monogenean eggs (Chisholm and Whittington, 2002;Sharp et al, 2004;Sitjà-Bobadilla et al, 2006;Thoney, 1990). This contrasted with our results and suggested that the effect of praziquantel on egg viability might depend on the monogenean species.…”
Section: Discussioncontrasting
confidence: 82%
See 2 more Smart Citations
“…Bath treatment with praziquantel has been tested against monogenean infections in fish (Schmahl & Mehlhorn 1985, Moser et al 1986, Buchmann 1987, Schmahl & Taraschewski 1987, Schmahl et al 1989, Buchmann et al 1990, Szekely & Molnar 1990, Thoney 1990, Santamarina et al 1991, and in many cases has proved effective. The common treatment scheme in these studies was exposure of fish to a concentration of less than 30 ppm praziquantel for at least 3 h. In commercial rockfish culture farms, however, the bathing of fish for such a long time is very laborious and severely stressful to the fish.…”
mentioning
confidence: 99%